2015
DOI: 10.1177/1087054715616185
|View full text |Cite
|
Sign up to set email alerts
|

The Associations Between Pre- and Postnatal Maternal Symptoms of Distress and Preschooler’s Symptoms of ADHD, Oppositional Defiant Disorder, Conduct Disorder, and Anxiety

Abstract: Objective: To examine the association between perinatal maternal symptoms of anxiety or depression and preschooler's symptoms of ADHD-IA, ADHD-HI, ODD, and CD, and whether associations varied by time of exposure or gender.Method: Children, aged 3.5 years (n = 1195), recruited from the Norwegian Mother and Child Cohort Study, were assessed with a semi-structured psychiatric interview.Questionnaires (SCL-5) provided information about perinatal maternal symptoms of anxiety and depression. We used mixed effect Poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 50 publications
2
38
0
Order By: Relevance
“…Using data from the Western Australian Pregnancy Cohort ( N  = 1214), Herbison et al found that prenatal stress was positively associated with depression/anxiety symptoms at age 20 in male but not female offspring after adjusting for postnatal childhood stress trajectories [55]. In the Preschool ADHD study, Bendiksen et al [39] found no evidence of sex dependence in the association between maternal prenatal anxiety and depression symptoms and early childhood anxiety symptoms [39]. Finally, in a case-control study ( N  = 1258), Gilman et al evaluated the association between maternal inflammatory cytokines and odds of major depressive disorder (MDD) in adult offspring (mean age 39.7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using data from the Western Australian Pregnancy Cohort ( N  = 1214), Herbison et al found that prenatal stress was positively associated with depression/anxiety symptoms at age 20 in male but not female offspring after adjusting for postnatal childhood stress trajectories [55]. In the Preschool ADHD study, Bendiksen et al [39] found no evidence of sex dependence in the association between maternal prenatal anxiety and depression symptoms and early childhood anxiety symptoms [39]. Finally, in a case-control study ( N  = 1258), Gilman et al evaluated the association between maternal inflammatory cytokines and odds of major depressive disorder (MDD) in adult offspring (mean age 39.7).…”
Section: Resultsmentioning
confidence: 99%
“…Among female offspring, there was greater evidence for positive associations between PNMS and early childhood difficulties with cognitive [48, 67] and motor development [41•, 66], and adulthood cardiovascular disease risk [60]. In contrast, we uncovered greater evidence for PNMS sensitivity in male offspring for early childhood wheezing/asthma [58•, 59], externalizing pathology [39, 54], and schizophrenia spectrum disorders [42•]. It is noteworthy that males have a greater risk in the general population for all of the adverse health outcomes showing male-biased PNMS programming effects in this review (early childhood asthma/wheezing [58•, 59, 74], externalizing pathology [39, 54, 75], and schizophrenia spectrum disorders [42•, 76]).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, the Behavior Outlook Norwegian Developmental Study (BONDS) is a Norwegian study initiated in 2006 following the development of social competence and behavioral problems in 1159 children (Naerde et al, 2014). The Norwegian Mother and Child Cohort study (MoBa), with a consecutive enrollment between 1999 and 2008 including 111 000 pregnant women and their children, is yet another prospective longitudinal study including aspects of child mental health (Bendiksen et al, 2015). In the Danish Copenhagen Child Cohort (DCCC) including 6090 children followed from birth to preadolescence, prevalence and risk factors for psychiatric disorders have been examined (Elberling et al, 2016).…”
Section: Longitudinal Studiesmentioning
confidence: 99%